Cuando el virus "pintó" una presentación inusual - Marta Azevedo Ferreira; Joana Marques (Sociedade Galega de Medicina Interna, 2024)
We present the case of a purpura secondary to COVID-19 with exuberant dermatological manifestation without any other systemic symptoms.